KEPUTUSAN PEMBELIAN KONSUMEN PADA COFFEE SHOP SUGENG KOPI DITINJAU DARI MEDIA SOSIAL, VARIASI PRODUK, DAN EXPERIENTIAL MARKETING - Sindi Tissa Safira (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this research is to determine whether consumer purchasing decisions affect social media, product variations, and experiential marketing at the Sugeng Kopi coffee shop. This type of research is quantitative. The data collection technique used multiple linear regression. The number of samples taken was 100 respondents. The data were R analyzed through the validity test, reliability test, normality test, heteroscedasticity test, multicolonearity test, multiple linear regression test, f test, t test, and determination coefficient test (R2). Based on the results of data analysis, it shows that the results of research on purchasing decisions have a positive and significant effect on social media. Purchasing decisions have a positive and significant effect on product variation. Purchasing decisions have a positive and significant effect on experiential marketing. This shows that consumer purchasing decisions simultaneously influence social media, product variations, and experiential marketing at the Sugeng Kopi coffee shop. Keywords: purchasing decisions; social media; product variety; experiential marketing